Transboundary Cooperations in Rwanda: Organisation Patterns of Companies, Projects, and Foreign Aid Compared - Pohl, Robin (transcript, 2016)
How is transnational cooperation practically conducted in the East African country of Rwanda, and how is it organised? Can the worlds of development aid and private business be compared?In this ethnography, Robin Pohl identifies the organisational patterns used by Rwandan, European and Indian partners. Different types of agencies, companies or projects each relate foreign activities differently to their local environment. The effects of potential divisions at the global level turn into assets or liabilities on the operative level of transboundary cooperations, depending on their context.